Cozina gaining insight into the eating and cooking habits of young adults living independently in Quezon City - Genuino, Ruth Aurora F.
With the decline in the importance of home food preparation in the urban household in Metro Manila, emerging young adults have less exposure to cooking and healthy eating. This leads to young adults developing poor dietary behaviors when living alone. This research aims to gain insight into the relationship of the transitional period of leaving home to the change in eating and cooking behaviors of young adults living in Quezon City, and create an effective visual communication-based intervention that promotes positive eating and cooking behaviors.